Clinical features, treatment, and prognosis of different histological types of primary small bowel adenocarcinoma: A propensity score matching analysis based on the SEER database. Issue 8 (August 2021) - Zhou, Yu-Wen; Xia, Ruo-Lan; Chen, Yue-Yun; Ma, Xue-Lei; Liu, Ji-Yan
Abstract: Purpose: This aim of this study was to provide a comprehensive understanding of the clinical characteristics, treatment, and prognosis of patients with small bowel adenocarcinoma (SBA), mucinous small bowel adenocarcinoma (MSBA), and signet ring cell carcinoma of the small bowel (SRCSB). Methods: Information on patients with SBA, MSBA, and SRCSB (2004–2015) was obtained from the Surveillance, Epidemiology and End Results (SEER) database. Cox proportional hazards models and Kaplan–Meier curves were used for the survival analyses. Propensity-score matching (PSM) was implemented to determine the differences among these tumors. Results: In all, 3697 patients with SBA (n = 3196), MSBA (n = 325) and SRCSB (n = 176) were ultimately eligible for this study. Poor differentiation, local invasion, and lymph node metastasis were more likely to be observed in SRCSB than in SBA and MSBA. Surgery was the most common treatment modality in all groups. The prognosis of SBA was similar to that of MSBA, but better than that of SRCSB in both unmatched and matched cohorts. M stage, surgery, and chemotherapy were identified as independent predictors of survival in all patients. Surgery and chemotherapy could significantly improve outcomes in all groups before and after PSM. Radiotherapy was associated with a survival benefit in patients with SBA, but this trend was not maintained after PSM. Survival advantages of SBA and MSBA were remarkable in the stratified analysis of surgery after PSM. Conclusion: Patients with SRCSB had the worst prognosis among all histological types examined. However, surgery and chemotherapy could improve patients survival, regardless of histological type.